Exploring Students’ and Teachers’ Perceptions towards the Use of Mind-Mapping Technique to Improve Learners’ Writing Performance Case of Second Year EFL Students at Souk –Ahras University - RAHAL Souraya (My University, 2024)
Abstract The current study aims to explore the perceptions of EFL students and teachers regarding the use of the mind mapping technique to improve the writing performance of second-year EFL students at the University of Mohamed Cherif Messadia, Souk-Ahras. Additionally, it investigates the contribution of implementing mind mapping in enhancing students' writing performance and the extent to which it aids teachers in guiding students' writing. To address these objectives, an exploratory research design was employed, utilizing two data gathering tools: a printed questionnaire administered to 41 students and an interview conducted with 7 EFL teachers from the same department. The obtained results indicate that both EFL students and teachers hold positive perceptions regarding the effectiveness of mind mapping in enhancing learners' writing performance. Furthermore, it was found that the use of mind mapping can significantly assist teachers in supporting students' writing performance.However,the study also revealed that EFL students encounter various challenges when implementing the mind mapping technique in their writing.The hypotheses formulated based on these results are validated. Finally, recommendations and suggestions for further research are proposed. -------------------- الملخص تهدف الدراسة الحالية إلى استكشاف تصورات الطلاب والمعلمون في اللغة الإنجليزية بشأن استخدام تقنية الخرائط الذهنية لتحسين الأداء في الكتابة لطلاب السنة الثانية في اللغة الإنجليزية في جامعة محمد الشريف مساعدية بسوق أهراس. بالإضافة إلى ذلك، فإنها تبحث في مساهمة تنفيذ تقنية الخرائط الذهنية في تعزيز أداء الطلاب في الكتابة ومدى مساعدتها للمعلمين في توجيه كتابة الطلاب. لمعالجة هذه الأهداف، تم استخدام تصميم بحث استكشافي، باستخدام أدوات جمع بيانات: استبيان مطبوع أُدرج على 41 طالبًا ومقابلة أُجريت مع 7 معلمين في اللغة الإنجليزية من نفس القسم. تشير النتائج المحصلة إلى أن الطلاب والمعلمين في اللغة الإنجليزية يحملون تصورات إيجابية بشأن فعالية تقنية الخرائط الذهنية في تحسين أداء تعلم الكتابة. علاوة على ذلك، تبين أن استخدام التصور بشكل كبير يمكن أن يساعد المعلمين في دعم أداء الطلاب في الكتابة.مع ذلك كشفت الدراسة ايضا ان طلاب اللغة الانجليزية كلغة اجنبية يواجهون تحديات متنوعة عند تنفيذ تقنية الخرائط. تم تحقيق الفرضيات التي صيغت بناءً على هذه النتائج. وأخيرًا، يتم اقتراح توصيات واقتراحات للبحوث المستقبلية ----------------- Résumé La présente étude vise à explorer les perceptions des étudiants et des enseignants en anglais concernant l'utilisation de la technique de mind mapping pour améliorer les performances en écriture des étudiants de deuxième année en anglais à l'Université de Mohamed Cherif Messadia, Souk-Ahras. De plus, elle examine la contribution de la mise en œuvre du mind mapping dans l'amélioration des performances en écriture des étudiants et dans quelle mesure cela aide les enseignants à guider l'écriture des élèves. Pour atteindre ces objectifs, une conception de recherche exploratoire a été utilisée, en utilisant deux outils de collecte de données : un questionnaire imprimé administré à 41 étudiants et une entrevue menée avec 7 enseignants en anglais du même département. Les résultats obtenus indiquent que tant les étudiants en anglais que les enseignants ont des perceptions positives concernant l'efficacité du mind mapping dans l'amélioration des performances en écriture des apprenants. De plus, il a été constaté que l'utilisation du mind mapping peut aider de manière significative les enseignants à soutenir les performances en écriture des étudiants.Cependat, l’etude a egalement rèlèvè que les etudiants en ALE recontrent diversesdifficultes lors de la mise en oeuvre de la technique de mind mapping daans leur rèdaction. Les hypothèses formulées sur la base de ces résultats sont validées. Enfin, des recommandations et des suggestions pour de futures recherches sont proposées.